Is there variation in the response to contact call playbacks across the hybrid zone of the parrot Platycercus elegans?. (27th March 2013) - Ribot, Raoul F. H.; Berg, Mathew L.; Buchanan, Katherine L.; Bennett, Andrew T. D.
<x xml:space="preserve">Abstract</x> Learned vocal signals could be important in the formation of prezygotic isolation between two hybridising taxa. This study examined whether vocal variation in the parrot Platycercus elegans facilitates the separation of individuals from two subspecies, P. e. elegans (CR) and P. e. flaveolus (YR). CR and YR have very different plumage coloration, respectively deep crimson and pale yellow, but hybridise where they meet creating an intermediate population (WS). In a factorial design playback experiment, we conducted 108 playback trials on three focal populations (YR, WS, CR), in and around this area of hybridisation, to test if they respond differently to contact calls from their own or another population. We also analysed whether differences in acoustic variables of the stimulus calls predicted the response to the call. We did not find any indication that individuals from the three focal populations responded differently to calls sampled from their own or another subspecies. We did find an effect of two of the five acoustic variables that we used to describe and classify contact calls from the three source populations. Specifically, duration of the stimulus call positively affected the response from individuals from WS and negatively the response from CR, and CR responded more to stimulus calls with a lower peak frequency. Overall, we found no indication that acoustic variation in contact calls on a subspecies level is involved in maintaining plumage colour differences between P. e. elegans and P. e. flaveolus subspecies.